Transforaminal Intrathecal Access for Injection of Nusinersen in Adult and Pediatric Patients with Spinal Muscular Atrophy - Shokuhfar, Tahaamin; Abdalla, Ramez N.; Hurley, Michael C.; Nazari, Pouya; Ansari, Sameer A.; Ajroud-Driss, Senda; Kuntz, Nancy; Azmi, Subhan; Rao, Vamshi; Shaibani, Ali (Journal of Pediatric Neurology, 2020)
The main purpose of this article is to assess the safety and efficacy of transforaminal lumbar puncture for the injection of nusinersen (Spinraza) in patients with extensive spinal fusion and/or scoliosis.A retrospective chart reviews of all spinal muscular atrophy patients (adults and children) were conducted. Demographic data, procedure details, follow-ups, and related complications were recorded.We performed 85 transforaminal injections in nine pediatric patients (5 male and 4 female) aged between 8 and 17 years (mean = 11 years) and seven adult patients (5 females and 2 males) aged between 24 and 41 years (mean= 30 years). Fluoroscopy guidance was used in 87% of our patients. No major complication was reported.Fluoroscopy-guided transforaminal nusinersen injection is a safe and successful alternative approach in adult and pediatric patients with severe spinal scoliosis, interlaminar osseous fusion, and spinal fusion hardware.
Keywords: spinal muscular atrophy; transforaminal; lumbar puncture